Constrained by localized attention focus: The negative effect of firm-specific knowledge on exploratory firm innovation - SULLIVAN, Bilian Ni (Institutional Knowledge at Singapore Management University, 2023)
Integrating the resource-based view (RBV) and attention-based view (ABV), this study explores the impact of firm-specific knowledge (FSK) on a firm's exploratory innovation and the role of government support in this process. We argue that firms with a high degree of specificity in their knowledge assets tend to have a more localized attention focus, leading to those firms with less exposure to distant and diverse information and knowledge. Consequently, such firms are likely to have reduced exploratory innovative outputs. However, government resource support could expand a firm's attention focus beyond local searches, mitigating its negative effects. Based on a unique combined two-wave survey and archival data from over 500 firms in China, we find that the level of FSK is negatively related to a firm's exploratory innovation output. We provide evidence that localized attention focus partially mediates the negative effect of FSK on firms' exploratory innovation. We further reveal that state ownership and state financial support for firm innovation weaken the negative main effect. This study makes important contributions to the literatures on the RBV, FSK, and firm innovation.